Virtual and Mixed Reality - Systems and Applications International Conference, Virtual and Mixed Reality 2011, Held as Part of HCI International 2011, Orlando, FL, USA, July 9-14, 2011, Proceedings, Part II - Shumaker, Randall (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2011)
The two-volume set LNCS 6773-6774 constitutes the refereed proceedings of the International Conference on Virtual and Mixed Reality 2011, held as Part of HCI International 2011, in Orlando, FL, USA, in July 2011, jointly with 10 other conferences addressing the latest research and development efforts and highlighting the human aspects of design and use of computing systems. The 47 revised papers included in the first volume were carefully reviewed and selected from numerous submissions. The papers are organized in the following topical sections: VR in education, training and health; VR for culture and entertainment; virtual humans and avatars; developing virtual and mixed environments.